Levantamiento de un inventario de dulces tradicionales presentes en el centro histórico de Quito - Proaño Bohórquez, Estefanía Gabriela (2020)
Stocktaking of Traditional Sweets in Quito’s Historic Center. For which, both bibliographic and field research was carried out. Bibliographic research was based on documents, books, magazines, among others demarcating itself in the city of Quito to publicize the history and definitions of confectionery, the Historic Center’s characteristics, and the whole background of the sweets. Field research was based on technical visits to food managers and collecting information on traditional sweets through surveys. There was Information gathered on the ingredients, recipes, and procedures. In addition, how they inherited the knowledge about these products was also one of the investigation discoveries. It was concluded that a stocktaking of traditional sweets is extremely significant as it allows for the identity and gastronomic culture in the Historic Center to be preserved. Additionally, it is substantial to make traditional confectionery known to new generations.